"A valid electoral exercise"? Uganda's 1980 Elections and the Observers' Dilemma. (25th January 2017) - Willis, Justin; Lynch, Gabrielle; Cheeseman, Nic
Abstract: The presence at Uganda's 1980 general elections of a Commonwealth Observer Group might be seen as a seminal moment. This was the first formal international observation of polls in a sovereign African state and the precursor of multiple similar missions that later became routine. Yet the 1980 mission sits uneasily in the history of election observation. The observers endorsed the results despite evidence of malpractice, and Uganda plunged into civil war within months. Internationally, the mission is now either forgotten or treated as an embarrassment. Within Uganda, it has been denounced as part of an outsider conspiracy to foist an unwanted president on an unwilling people. This article argues that the 1980 mission was neither entirely seminal nor an aberration, and that both the elections and observation were driven partly by actors within Uganda rather than simply imposed by outsiders. The availability of UK government records allows us to see the events of 1980 as a particularly clear example of a recurring "observers' dilemma." Ideally, elections combine democracy and state-building. They offer people a choice as to who will lead or represent them, and at the same time they assert through performance a crucial distinction between a capable, ordering state and a law-abiding citizenry. Yet these two aspects of elections may be in tension; a poll that offers little or no real choice may still perform "stateness" through substantial, orderly public participation. When that happens in what would now be called a "fragile state, " should international observers denounce the results?